2019
DOI: 10.1177/2043610619863069
|View full text |Cite
|
Sign up to set email alerts
|

Adultization and blurring the boundaries of childhood in the late modern era

Abstract: Although the modern Western concept of childhood is rapidly disappearing in the age of late modernity, this study asserts that childhood (as it is lived) has not disappeared but has been transformed. An integrated approach to childhood is employed in order to go beyond binary oppositions such as the Global North versus the Global South and/or childhood versus childhoods. It is argued that children while constructing their childhoods are confronted with processes of individualisation and globalisation through w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 56 publications
(82 reference statements)
0
7
0
1
Order By: Relevance
“…Firinci Orman's concept of adultization breaks down the binary of either negative or positive framings of modern children's experiences. Rather, as our results reflect, food insecurity presents children with both 'dangers and opportunities' [47] (p. 111).…”
Section: Discussionmentioning
confidence: 50%
See 4 more Smart Citations
“…Firinci Orman's concept of adultization breaks down the binary of either negative or positive framings of modern children's experiences. Rather, as our results reflect, food insecurity presents children with both 'dangers and opportunities' [47] (p. 111).…”
Section: Discussionmentioning
confidence: 50%
“…Our study has responded directly to such calls and confirms that children are important voices in providing profound, fine-grain evidence of the impact of socioeconomic disadvantage on food access. The children in this study understood food insecurity in relational ways and their experiences demonstrate the ways in which adultization of childhood presents both dangers and opportunities for children as family members and, more broadly, as citizens [47]. The accounts showed that, whether through first or second-hand experience, children described food insecurity through their relationships with other people, through concern and empathy for peers, fear of siblings taking their food, the ebb and flow of house guests coming and going, or care and concern for a hungry father.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations